Rancang Bangun Web Company Profile Pada Wedding Organizer Master Tenda Menggunakan Framework Codeigniter - Fitri Rizky Mardani; Moch Farid Fauzi (LPPM STMIK IKMI Cirebon, 2023)
Master Tenda is a business engaged in wedding organizer services in Sekadau Hilir District, Sekadau Regency, West Kalimantan. Information about the current Master Tenda wedding organizer is by utilizing personal relationships and social media such as Facebook and Instagram. The use of relations is inappropriate because this method only focuses on a small circle of connections in the environment around Sekadau Hilir District, Sekadau Regency. This research aims to produce a web company profile that is useful to support the information delivery process at the Master Tenda wedding organizer. This study uses the Waterfall research method, which consists of needs analysis, system design, design, testing, and maintenance. This system was created using the PHP programming language MySQL as a database and with the help of the Visual Studio Code application. The result of this research is a company profile website on the Master Tenda wedding organizer, which is expected to be a medium for conveying information on the Master Tenda wedding organizer. Master Tenda merupakan usaha yang bergerak dibidang pelayanan jasa wedding organizer di Kecamatan Sekadau Hilir, Kabupaten Sekadau, Kalimantan Barat. Informasi mengenai wedding organizer Master Tenda saat ini yaitu dengan memanfaatkan relasi dan media sosial seperti facebook dan instagram milik pribadi. Pemanfaatan relasi dirasa kurang tepat karena cara ini hanya berfokus pada lingkaran relasi yang kecil di lingkungan sekitar Kecamatan Sekadau Hilir, Kabupaten Sekadau. Tujuan dari penelitian ini yaitu untuk menghasilkan web company profile yang berguna untuk mendukung proses penyampaian informasi di wedding organizer Master Tenda. Penelitian ini menggunakan metode penelitian Waterfall yang terdiri dari analisa kebutuhan, desain sistem, perancangan, pengujian dan pemeliharaan. Sistem ini dibuat dengan menggunakan bahasa pemrograman PHP, MySQL sebagai database dan dengan bantuan aplikasi Visual Studio Code. Hasil penelitian ini adalah adanya website company profile pada wedding organizer Master Tenda yang diharapkan dapat menjadi media dalam penyampaian informasi wedding organizer Master Tenda.